Pathogenicity in Chicken Anemia Virus with Eimeria tenella: Concurrent Co-Infection and Secondary Eimeria tenella Infection - Chung, Hsyang-Hsun; Tongkamsai, Suttitas; Cheng, Ming-Chu; Tsai, Yi-Lun; Lee, Meng-Shiou; Lien, Yi-Yang; Chen, Ya-Mei (Microorganisms (Basel), 2025)
Chicken anemia virus (CAV) and Eimeria tenella (E. tenella) are economically important pathogens of the poultry industry worldwide. However, the impact of dual infection of these two pathogens in chickens remains unclear. This study investigated the pathogenic effects of dual infection with CAV and E. tenella using two trials. In Trial A, chickens were infected at 21 days of age (D21) with either CAV and E. tenella simultaneously (C21 + T21), CAV alone (C21a), E. tenella alone (T21), or PBS as a negative control (NC). In Trial B, chickens received CAV at D21 followed by E. tenella at D28 (C21 + T28), CAV alone at D21 (C21b), E. tenella alone at D28 (T28), or PBS at D21 (NC). Assays of lesion scores (LS), oocysts per gram (OPG) of feces, packed cell volume (PCV), and thymus index (TI) were used to assess variations in pathogenicity. Both the C21 + T21 and C21 + T28 groups showed higher OPG than the group infected with E. tenella alone, with significantly elevated OPG in the secondary infection scenario and more severe lesions in the concurrent co-infection group (p < 0.05). Anemia, indicated by PCV < 27%, was observed in the C21 + T21 group at day 28 and in the C21 + T28 group at day 35, both of which had significantly lower PCV values than the group infected with CAV alone (p < 0.001). Thymus atrophy was most severe in C21 + T21 at 28 days old (p < 0.05; p < 0.01). In this study, preliminary observations suggested that concurrent and secondary infections with CAV and E. tenella showed variable trends that may indicate potential interactions; however, these exploratory findings require more systematic validation in older chickens.